Thailand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on Thailand reviews public investment and investment recovery from financial crises. Thailand is a country with a moderate tax effort, which indicates that increases in public saving should be achieved through a mixture of tax and expenditure measures. Future budgets should accommodate the megaprojects without putting excessive pressures on public finances, inflation, and the external balance. Least present value of revenue (LPVR) auctions alleviate the demand risk inherent in the fixed-term contracts and thus eliminate a key driver for renegotiations and the provision of minimum income guarantees.